CONDITION OF THE MANGROVE FOREST AT UNIVERSITAS RIAU MARINE STATION, DUMAI - Siregar, Rifa Ghina Aulia; Efriyeldi, Efriyeldi; Mulyadi, Aras (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Mangrove plant communities grow well in tropical regions and adapt to extreme environmental conditions. The coastal area of Dumai is filled with various activities in the form of industry, ports, agriculture, and settlements. The complexity of activities on the beach greatly affects the balance of the ecosystem. This study aimed to determine the composition of mangrove forest species and conditions based on density value, importance index, percentage of canopy cover, and mangrove stand height. The survey method used in this study, where the data collected is primary data. There are four species of mangroves, including Rhizophora apiculata, Bruguiera gymnorriza, Xylocarpus granatum, and Sonneratia alba. The density of mangroves is in good condition, with dense densities ranging from 2067-3266.67 ind/ha. Canopy closure in good condition ranges from 76.12-80.45%. The highest important value index is R. apiculata, with a value of 159.64%, and the lowest is B. gymnorriza, 13.77%. The highest stand was S. alba, with a value of 18.84 m, and the lowest was X. granatum, with a value of 10.60 m.